PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA CANVA DALAM MENINGKATKAN KEMAMPUAN MENULIS PUISI SISWA SMP - Annisa Lishandi; Euis Eti Rohaeti; Alfa Mitri Suhara (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to determine the effectiveness of the implementation of the Project Based Learning model assisted by Canva media in improving the poetry writing skills of junior high school students. The background of this study is based on emphasizing the importance or writing to improve creativity, and active student involvement in learning activities. The purpose of the study was to determine students writing skills using the Project Based Learning model, this project can encourage students to be more creative in completing poetry literary work projects. The research method used is quantitative descriptive. Data collection techniques are carried out through observation sheets, response questionnaires, and analysis of students poetry literary works. The results of this study indicate that the implementation of the Project Based Learning model assisted by Canva media can improve students poetry writing skills, at the first meeting the results were 80% and the second meeting 100% observed by the observer. The students questionnaire responses to the learning obtained 76%. The pretest result showed that the average initial ability of students in writing poetry texts was 47,63%. After being given learning treatment with the Project Based Learning model based on projects and assisted by Canva media, the average student score increased significantly to 88,27% in the posttest. In addition to the increase in score, the resulting poetry literary works showed a more precise and creative mastery of the elements of poetry. This study shows that the Project Based Learning model assisted by Canva media is effective in helping students develop their ability to write poetry appropriately and optimally.